Impact of Financial Development on Inclusive Growth in Nigeria: Array - Kazeem, Bayo (The Journal of Accounting and Management, 2021)
This study examined the impact of financial development on inclusive growth in Nigeria using a time series data obtained from secondary sources between 1999 and 2019. Financial development was measured using broad money supply and domestic credit to private sector, while inclusive growth was measured from income perspective using per capita GDP and from expenditure perspective using household consumption expenditure. The data were mainly obtained from World Development Indicators database. The data were analysed using Autoregressive Distributed Lag (ARDL) Bound test approach. The results of the ARDL revealed that financial development proxy with broad money supply exert significant positive impact on per capita income and household consumption expenditure in both short and long run. On the contrary, domestic credit to private sector has significant negative impact on per capita income in short and long run while the impact on household consumption expenditure was not significant in both short and long run. The study concluded that financial development represented by broad money supply is crucial to inclusive growth in Nigeria. The research therefore recommends that the government should use Broad Money Supply as one of the financial development instruments to promote inclusive growth in Nigeria.